4D printing of shape memory composites with remotely controllable local deformation. (April 2023) - Ren, L.; Wang, Z.; Ren, L.; Liu, Q.; Li, W.; Song, Z.; Li, B.; Wu, Q.; Zhou, X.
Abstract: Shape memory polymers with multiple temporary shapes have shown great potential for applications in biomedical, aerospace, and intelligent robotics fields. However, the realization of the multiple shape memory properties of shape memory polymers is currently mostly dependent on formula design. Here, we report a strategy to remotely program the local bending behavior of shape memory composites using an infrared light source. The infrared light source is used to locally activate a single side of the sample with a temporary shape, which induces an asymmetric shape recovery due to the temperature gradient along the thickness direction, and achieves the phototropic response on-demand bending deformation. We exerted control over the bending deformation of the composite prototypes by devising the 3D printing parameters, infrared light intensity, and temporary shape programming. As a demonstration case, we designed and prepared a hand-like structure that can be bent sequentially, a flower whose petals can be excited to fold sequentially, and a digital logic circuit for sequential lighting of LEDs. Graphical abstract: Image 1 Highlights: A new 4D printing strategy was developed for remote control of local deformation of 2D films of shape memory composites (SMCs). The printing parameters, prestrain, and infrared light power can program the local deformation of SMCs 2D films. After local stimulation removal, the deformed structure remained unchanged. The proposed 4D deformation strategy can be extended to other SMCs.